Distinguishing between enduring and dynamic concussion symptoms: applying Generalisability Theory to the Rivermead Post Concussion Symptoms Questionnaire (RPQ) - Medvedev, Oleg N.; Theadom, Alice; Barker-Collo, Suzanne; Feigin, Valery; BIONIC Research Group (PeerJ, 2018)
Background The Rivermead Post Concussion Symptoms Questionnaire (RPQ) is a widely-used, 16-item measure of concussion symptoms yet its ability to assess change in the symptom experience over time has come under criticism. We applied Generalisability theory to differentiate between dynamic and enduring aspects of post-concussion symptoms and to examine sources of measurement error in the RPQ. Materials and Methods Generalisability theory was applied using the longitudinal design with persons as the object of measurement. Patients with a traumatic brain injury (n = 145; aged ≥16 years) were assessed at three time occasions (1, 6 and 12 months post-injury) using the RPQ. Results The RPQ showed overall strong generalisability of scores (G = .98) across persons and occasions with a minor proportion of variance attributed to the dynamic aspect of symptoms reflected by interaction between person and occasion. Items measuring concentration, fatigue, restlessness and irritability reflected more dynamic patterns compared to more enduring patterns of sensitivity to noise, impatience, nausea and sleep disturbance. Conclusion The RPQ demonstrated strong reliability in assessing enduring post-concussion symptoms but its ability to assess dynamic symptoms is limited. Clinicians should exercise caution in use of the RPQ to track dynamic symptom change over time. Further investigation is necessary to enhance the RPQ’s ability to assess dynamic symptoms and to address measurement error associated with individual items.
Keywords: Rivermead Post Concussion Symptoms Questionnaire; Trait; Generalisability Theory; Measurement; Psychometrics; State